Epistemology of Contemporary Calligraphy Art in Shaping The Character of Students - Fauziyah, Himmatul; Suparjo (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Di modern era as it is today, the skills and creativity of visual arts (image) students in Madrasah Ibtidaiyah still less associated with religious values. Contemporary calligraphy art with its visual beauty and deep spiritual value, offers great potential in shaping the character of students, especially in learning the Qur'an Hadith in Madrasah Ibtidaiyah. Epistemology as a branch of philosophy that discusses how the process of obtaining knowledge and what things need to be considered to obtain trueknowledge. Thepurpose of this study is to determinethe contribution epistemologiof contemporary calligraphy epistemologyin shaping the character of students. Themethod diused by peneliti is a literature study that can be taken from various library sources such as books, journals, documents, and other historical stories. From the results of the literature study it was found that the art of contemporary calligraphy in learning the Qur'an Hadith can achieveentuk the character of Madrasah Ibtidaiyah students by utilizing spiritual values, visual aesthetics, digital technology, social culture and the rules contained in the calligraphy.